Representations of patients, family and health team around infant-juvenile diabetes and possible ways to approach: Analysis of the nutrition workshops carried out in 2016 in a Hospital in San Miguel de Tucuman, Argentina - Oliszewski, Denisse (Población y Salud en Mesoamérica, 2020)
Objective: It seeks to highlight the tensions that arise in a public health institution of San Miguel de Tucumán, Argentina in relation to the care and treatment of type 1 diabetes. Method: The reflections of this work present the conclusions to which it is up from a qualitative approach, of ethnographic approximation in the cycle of workshops of nutrition carried out in the Hospital of the child Jesus of San Miguel Tucumán, Argentina during 2016. The reflections of this work represent the conclusions to which it is up from the analysis of the ethnographic material obtained from the participant observation of the cycle of nutrition workshops carried out in the Hospital of the child Jesus of San Miguel Tucumán, Argentina during the 2016. They were aimed for diabetic patients-girls, boys and adolescents-and their parents. The information was obtained through the participant observation, in-depth interviews with patients, parents and members of the health team and the analysis of the written productions made in the workshops. Results: It is observed that there are different representations and interests among the actors involved which translate into difficulties in the communication; there is a adultcentric conception of childhood that does not attend to the present of patients and treats them more as "objects" of care than as "subjects", this hapens within the framework of an institutional culture that does not support its staff in the development of alternative care experiences such as the workshop device. Conclusions: the need to resignify the ways of understanding health, disease and childhood in the context of a chronic disease to help in adherence to treatment is noted.